2021
DOI: 10.3390/nu13020366
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Composition and Diversity of the Gut Microbiota in Relation to Habitual Dietary Intake in Korean Adults

Abstract: We investigated associations of habitual dietary intake with the taxonomic composition and diversity of the human gut microbiota in 222 Koreans aged 18–58 years in a cross-sectional study. Gut microbiota data were obtained by 16S rRNA gene sequencing on DNA extracted from fecal samples. The habitual diet for the previous year was assessed by a food frequency questionnaire. After multivariable adjustment, intake of several food groups including vegetables, fermented legumes, legumes, dairy products, processed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Preclinical studies for colon cancer suggest that consumption of mixed nuts, walnuts, and almonds inhibits DNA damage and tumor growth through the suppression of angiogenesis, proliferation, and inflammation, as well as increased apoptosis and favorable alterations to the gut bacteria and enterotype-like clusters [ 78 , 79 , 80 , 81 , 82 , 83 ]. In line with the latter, a cross-sectional study among 222 Koreans showed that a healthy dietary pattern characterized by higher intakes of nuts/seeds was related to higher α-diversity reflecting gut microbial health [ 84 ].…”
Section: Tree Nuts Peanuts and Cancermentioning
confidence: 96%
“…Preclinical studies for colon cancer suggest that consumption of mixed nuts, walnuts, and almonds inhibits DNA damage and tumor growth through the suppression of angiogenesis, proliferation, and inflammation, as well as increased apoptosis and favorable alterations to the gut bacteria and enterotype-like clusters [ 78 , 79 , 80 , 81 , 82 , 83 ]. In line with the latter, a cross-sectional study among 222 Koreans showed that a healthy dietary pattern characterized by higher intakes of nuts/seeds was related to higher α-diversity reflecting gut microbial health [ 84 ].…”
Section: Tree Nuts Peanuts and Cancermentioning
confidence: 96%
“…A similarity between the diets of Korean (52 million population, land area 100,200 km 2 ) and Japanese (127 million population, land area 378,000 km 2 ) is the heavy consumption of fermented foods such as fermented vegetables (e.g., kimchi, natto, and tsukemono), soybean paste, fish products, red pepper paste, medicinal herbs, and sesame or perilla oil ( Kim et al, 2016 ), originally developed to cover for shortfalls in food during winter. The intakes of fermented legumes, vegetables, and potatoes were found to be positively associated with higher α-diversity and F:B ratio in the Korean NAS-IARC cohort ( Noh et al, 2021 ). A metagenomic analysis of kimchi revealed dominating members of Leuconostoc , Lactobacillus , and Weissella ( Jung et al, 2011 ), with the latter recently isolated and identified in traditional Indian fermented foods ( Månberger et al, 2020 ).…”
Section: Regional Dietary Patterns and Associated Gut Microbiome Trendsmentioning
confidence: 98%
“…Even though studies have shown associations between diet and gut microbiota (26)(27)(28)(29)(30)(31), studies investigating metabolic markers associated with both gut microbiota and diet in healthy adults are scarce (32)(33)(34)(35). Identifying specific gut bacteria associated with both diet and metabolic markers may be valuable and could represent a potential strategy for the prevention of disease.…”
Section: Popular Scientific Summarymentioning
confidence: 99%